Birth by Cesarean Section and Educational Achievement in Adolescents. Issue 12 (December 2021) - Slykerman, Rebecca F.; Li, Eileen; Shackleton, Nichola; Milne, Barry J.
Abstract : (Abstracted from Aust N Z J Obstet Gynaecol 2021;61:386–393) Evidence suggests that the process for colonizing and stabilizing infant gut microbiota may affect cognitive outcomes later in life, through pathways that connect the gut with the central nervous system. As the fetus's gut undergoes rapid change, so does early brain pathway development.